Learning al-Ashwat al-'Arabiyah With the Application PAIKEM Model: An Ethnography Study at STAI Darul Qur'an Payakumbuh - Hasanah, Sari Uswatun; Yasmadi, Yasmadi; Rahmawati, Rahmawati (Ruhama : Islamic Education Journal, 2024)
Al-ashwat al-'Arabiyah as one of the language elements is important in foreign language learning, because the ability of ashwat becomes the basis and main foundation in learning other elements in the language. But in reality, students have difficulty in learning ashwat, therefore this study aims to analyse how the use of PAIKEM model in learning al-ashwat al-'arabiyyah. This research uses a qualitative approach with an ethnography design to analyse the effectiveness of PAIKEM implementation, student engagement, and learning outcomes achieved. Data were collected through classroom observation, in-depth interviews with students, and document analysis such as syllabus and lesson plans. The results showed that the implementation of PAIKEM significantly improved students' learning engagement and motivation. Students were more active in group discussions, simulations, and question and answer activities, which created a dynamic and interactive learning atmosphere. In addition, the use of varied learning media, such as videos, language games, interactive applications, and visual aids, helped students to understand the concept of Ashwat Al-Araby better. Students' academic scores also showed a significant improvement after the implementation of PAIKEM, with the average mid-semester exam score increasing. This study concludes that PAIKEM is an effective learning model to improve the learning quality of Ashwat al-Arabiy Science at STAI Darul Qur'an Payakumbuh. The results of this study are expected to be a reference for other educational institutions that want to adopt a similar approach.Keyword : Al-Ashwat al-'Arabiyyah, Learning, PAIKEM